(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
The administration of syariah is only a small part of the judicial works in the syariah courts in Malaysia. However, the administration is very important because it reflects the justice of syariah particularly if the jurisdiction of syariah courts is enlarged. This is because the enlargement of the jurisdiction would mean the increase in the prosecution before syariah courts. Such an increase in the criminal cases will test the integrity and competency of syariah courts in delivering justice. The observation in this article is from the constitutional perspective because the people are more aware of the constitution including fundamental rights issues. These issues need to be brought forward and discussed adequately. Therefore this article discusses several important constitutional issues relating to the adminstration of Syariah criminal justice such as the position of Islam in the Constitution, the legislative competency to enact syariah offences, independence of judiciary and powers of the related agencies. Keywords: administration of Syariah justice, Syariah courts, Syariah offences, fundamental rights